التفسير المقاصدي للقرآن الكريم - علي محمد أسعد (International Institute of Islamic Thought, 2017)
يهدف البحث إلى بناء اتجاه مقاصدي في التفسير، يقوم على التأصيل له ببيان أهم ركائزه من مقاصد القرآن الكريم وواجب المفسر؛ ما يتطلب ضبط مفهوم "المقاصد القرآنية" وتمييزها من مقاصد الشريعة، ثم إثبات مشروعية التفسير المقاصدي، وضبط مفهومه، وبيان أهميته، وعلاقته بالاتجاهات التفسيرية الأُخرى. The purpose of this study is to build an approach of the Gracious Qur'an interpretation based on 'Maqasid or its main intents. The pillars of such an approach are based on the intents and purposes of the Qur'an and the duty of the interpreter. This requires that the concept of the Qur'anic intents be understood clearly and distinguished from the intents of the Shari'a, and then to establish the legitimacy of the intents-based interpretation of the Qur'an, to understand its concept, and to clarify its importance and its relationship with other trends of Qur'an interpretation.